SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT BINA PERTIWI - ANFAS MAJDAN (2024)
PT Bina Pertiwi is a heavy equipment distributor company that focuses on the Material Handling sector. Currently the process of ordering goods at Pt. Bina Pertiwi is still done manually, customers have to come directly to the place to make transactions. This causes less sales activity effective. And requires a more effective sales method in order to expand the sales area. Because the use of manual documents such as giving invoices to customers using paper receipts is considered quite risky for recording incoming transactions because they can be lost. Therefore, a sales information system is needed as a tool help to record data, process data and integrate it. This aims to help companies have a digital platform that can competein today's global business environment. The main objective of this study project isto develop an online sales media design in the form of a website to increase sales activities and expanding the sales network, making it easier for companies to store sales transaction data. The development approach used in designing this system is waterfall. The result of this research is a web-based Sales Information System for PT. Bina Pertiwi is capable of recording, processing and integrating data, as well as providing structured data storage.